Gomphus kinzelbachi Schneider, 1984, in Iran: identification, habitat and behaviour (Odonata: Gomphidae) - Schneider, Thomas; Ikemeyer, Dietmar; Ferreira, Sónia; Müller, Ole (Zootaxa, 2017)
Gomphus kinzelbachi was described by Wolfgang Schneider (1984) on the basis of a single teneral male captured by B. L. Sage on the Alwand River in eastern Iraq. In late April to early May 2016 two of the authors (TS and DI) discovered three individual-rich populations of this species on the large lowland river Karkeh in southwestern Iran (Khuzestãn). This is the first report of a breeding population of this species. Based on collected material we confirmed the structural differences of the male secondary genitalia between G. kinzelbachi and G. davidi on a larger number of animals. The female of the species is described. Gomphus kinzelbachi resembles most closely G. davidi, compared to all other West-Palearctic Gomphus species. Therefore, a direct comparison of the two species is given, and additionally some differential diagnostic hints for two other Gomphus species reported from Iran is provided. Our observations suggest that G. kinzelbachi reproduces on large clean lowland rivers in SE Iraq and SW Iran. In SW Iran only a free flowing stretch of the Karkeh, one of three parallel rivers (Karkeh, Karoon, Dez), seems to be suitable for this species. The other two rivers are affected by dams, dam construction, and increasing salinization. Additional dam constructions are also planned on the Karkeh River, thus, G. kinzelbachi may be on the brink of extinction.